Unilateral conjunctival Classic Kaposi Sarcoma following a COVID 19 booster - Emily White; Nicholas Fazio; Konstantinos Tourmouzis; Samuel Ryu; Paul T. Finger; Jodi Sassoon; Roger Keresztes; Timothy Chou; Kevin Kaplowitz; Robert Honkanen (American Journal of Ophthalmology Case Reports, 2024)
Purpose: We describe a case of Classic Kaposi's sarcoma in a functionally monocular patient following a COVID19 vaccine booster and provide compelling evidence that suggests the booster was a relevant co-factor in the initiation of the disease process. Observations: The patient presented with red, irritated conjunctival area described as “bubbling” in her right eye. While her past medical history includes hypercholesterolemia and hypertension, she had no history of a compromised immune system. Her ophthalmologic history is more complex including treatment for glaucoma. The patient has 20/20 uncorrected vision OD and LP OS. Due to her ocular co-morbidities, the patient initially received interferon alpha 2-B qid for 6 weeks. However, topical therapy failed to decrease the size of the conjunctival lesions. After referral to Radiation Oncology, the right eye/orbit was treated with electron beam therapy for 1 month which caused a marked decrease in the size and vascularity of the conjunctival lesions. A slow improvement continued during followup. Conclusion and importance: In that the vaccine booster preceded the cancer, it appears etiologic to the appearance of Kaposi's sarcoma. The patient's monocular vision and glaucoma complicated her treatment. This case expands on current concepts of cofactors needed for the development of Kaposi's sarcoma in that vaccine booster administration was relevant to tumor progression and both clinical and mechanistic evidence is presented to support this hypothesis.